PENGARUH LATIHAN SHOULDER PRESS DUMBELL DAN ONE ARM DUMBEL TERHADAP KEMAMPUAN SMASH DALAM PERMAINAN BOLA VOLI - Suriatno, Adi (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
the influence of split squat jump exercise on increasing the muscle limb muscle and the smash test in the game of volleyball at student of Mahli mah al-mahsun mahirir NW dasan tapen Lesson Year 2017. The main problem in this research is the influence of split squat jump exercise to increase leg muscle and the determination of smash in the game of volleyball on the students of mah al-mahsun mahin khidir NW dasan tapen Lesson Year 2015/2016. My aim is to see how far the limb muscle power increase and the smash accuracy. Based on the above problems, this research has the following objectives: 1) Want to know the effect of split squat jump exercise on leg muscle power in the students of MA al-mahsun khidir NW dasan tapen) Want to know the effect of exercise of influence of split squat jump exercise on smash precision on the students of MA al-mahsun khidir NW dasan tapen. The design of this study using One Group Pretest-Posttest Design. In the study population amounted to 60 students, while the number of samples in use amounted to 30 students, With sampling technique using propusive sampling. While for the type of research is experiment. In this research, data collection method used is action test method, documentation method and observation. Data analysis technique using t-test formula. From the results of data analysis, it can be concluded as follows: 1) The results of data analysis shows the value of t-value 8.932> t-table2.045, it can be concluded that There is the influence of split squat jump exercise on leg muscle power in the game volleyball on students students of MA al-mahsun khidir NW dasan tapen year lesson 2017. 2) shows the value of t-count 6.035> t-tabel2,045, it can be concluded that There is influence of split squat jump exercise on smash accuracy in the game